Comprehensive biochemical determination of the therapeutic and preventive effectiveness of herbal remedies for periodontal damage in rats that consumed fried sunflower oil - Selivanska, I.; Shumyvoda, Yu. (Journal of Education, Health and Sport, 2025)
Background. Periodontitis is one of the most common human diseases (more than 80% of the adult population of highly developed countries). In the pathogenesis of periodontitis, osteoporosis of the periodontal bone tissue plays a decisive role, which occurs as a result of a significant decrease in mechanical load on the jaws, a deficiency of osteostimulating factors (vitamin D, calcium, omega-3 polyunsaturated fatty acids, sex hormones), as well as as a result of the development of oral dysbiosis. To investigate the therapeutic and prophylactic effectiveness of multifunctional phytomedicines using a complex biochemical method based on the total determination of the degree of changes in the level of several biochemical markers of pathology and protection. Methods. Fried sunflower oil (FSO) was obtained by thermal peroxidation of ordinary unrefined sunflower oil at a temperature of 180℃ in the presence of a catalyst. Biological studies were conducted on white Wistar rats, which consumed a mixed feed containing 2 g/kg of FSO for 75 days. As phytopreparations, we used multifunctional products developed by us containing bioflavonoids, lysozyme, mint and amaranth seed extracts, as well as prebiotics and calcium citrate. Comparison phytopreparations («Kvertuline» and «Lysozyme-forte») were administered with feed at a dose of 300 mg/kg, starting from the 31st day of the experiment. One group of rats that consumed FSO received oral irrigation of the oral cavity with 2 ml of the «Mint + Amaranth Extract» dental elixir. Rats were euthanized, gums and alveolar process of the mandible were isolated. In the gum homogenates, biochemical markers of pathology were determined, namely the activity of elastase, urease and the content of malondialdehyde (MDA), as well as the level of biochemical markers of defense systems, namely the activity of lysozyme, catalase and the antioxidant-prooxidant index API was calculated. In the homogenate of bone tissue, the activity of acid (AP) and alkaline (ALP) phosphatases was determined, the calcium content was determined, and the mineralization index (MI) was calculated based on the AP/ALP ratio. The degree (in %) of the decrease in the level of pathology indicators (elastase, urease, MDA, acid phosphatase) and the increase in the level of protection markers (lysozyme, catalase, API, alkaline phosphatase, calcium, MI) was calculated, and based on these data, the therapeutic and prophylactic efficacy (TPE) of each herbal preparation was calculated. Results. It was found that the consumption of FSO increases the activity of elastase in the gums by 55.2 %, urease by 26 % and MDA content by 72.8 %, but reduces the activity of lysozyme by 27.7 %, catalase activity by 15.8 % and the antioxidant-prooxidant index API by 51.3 %. In the periodontal bone tissue, the consumption of FSO increases the activity of AP by 206.5 %, but reduces the activity of ALP by 23.6 %, the mineralizing index MI by 61.5 % and the calcium content by 20.3 %. In rats that consumed FSO on the background of herbal preparations, the activity of elastase, urease and MDA content increases significantly less and the activity of lysozyme, catalase and API index decreases significantly less. In periodontal bone tissue, when consuming FSO against the background of herbal remedies, the activity of AP increases significantly less (by 4 – 10 times), the activity of ALP decreases by 3 – 10 times less, and the MI index decreases by 1.5 – 3 times less. Consumption of FSO against the background of herbal remedies reduces the calcium content by 2 times less. Conclusion. The therapeutic and prophylactic efficacy (TPE) calculated according to these indicators in the gums was the highest (76.5 %) in the dental elixir. In the bone tissue, TPE was also the highest in the dental elixir.